2014
DOI: 10.1182/blood.v124.21.509.509
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Cytotoxicity of Ibrutinib and the BCL2 Antagonist, ABT-199(GDC-0199) in Mantle Cell Lymphoma (MCL) and Chronic Lymphocytic Leukemia (CLL): Molecular Analysis Reveals Mechanisms of Target Interactions

Abstract: Bruton tyrosine kinase (BTK) is critical to both normal B-cell development and the pathogenesis of B-cell malignancies. Ibrutinib is a recently FDA-approved small molecule irreversible inhibitor of BTK. In Phase II studies of single-agent ibrutinib in MCL (Wang ML et al, NEJM 2013) and CLL (Byrd JC, et al, NEJM 2013) the overall response rate was 68% and 89% (CR, PR, and PR with lymphocytosis), respectively, with PR as the best response in the majority of patients. Thus, not all patients respond and complete r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Previous studies investigating alternate therapeutic targets have suggested that MCL-1 downregulation sensitizes MCL to BCL-2 inhibition, and the combinatorial efficacy of ibrutinib and the BCL-2 inhibitor ABT-199 has clearly been demonstrated (22)(23)(24). Our proteomic profiling identified the downregulation of MCL-1 by BGB-3111 in Jeko-1 cells.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies investigating alternate therapeutic targets have suggested that MCL-1 downregulation sensitizes MCL to BCL-2 inhibition, and the combinatorial efficacy of ibrutinib and the BCL-2 inhibitor ABT-199 has clearly been demonstrated (22)(23)(24). Our proteomic profiling identified the downregulation of MCL-1 by BGB-3111 in Jeko-1 cells.…”
Section: Discussionmentioning
confidence: 60%
“…Preclinical data support the combination of the Bruton's tyrosine kinase inhibitor ibrutinib and the B-cell lymphoma 2 inhibitor venetoclax by demonstrating synergy in a diffuse large B-cell lymphoma cell line model and in primary CLL cells, as well as in mantle cell lymphoma cell lines. 11 Furthermore, several clinical trials are currently testing IV for clinical use, with no unexpected toxicities reported so far through scientific meetings, publications or internal reports for the marketing holders. Consequently, the aim of the current trial is to evaluate if combination treatment with venetoclax+ibrutinib in patients with RR-CLL can lead to MRD negativity and induce long-lasting remission even after stopping the treatment.…”
Section: Open Accessmentioning
confidence: 99%
“…also demonstrated that the ibrutinib and ABT‐199 combination displayed strong synergistic effects in MCL cell lines as well as primary cells from patients with recurrent MCL. Portell et al . reported, again at the ASH 2014 meeting, the synergistic effect of ibrutinib and carfilzomib or ABT‐199 on apoptosis of circulating tumor cells from patients with MCL.…”
Section: Mantle Cell Lymphomamentioning
confidence: 98%
“…Potential ibrutinib‐containing combination therapy for CLL has also been studied preclinically. Promising candidates to combine with ibrutinib included proteasome inhibitors, Bcl‐2 inhibitors, and IRAK1/4 kinase inhibitors . These combinations were somewhat better studied in other B‐cell malignancies and are described below.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%